Isolation and Electrochemical Evaluation of Electrogenic Bacteria from the Sediment of Two Waterlogged-Ecosystems - Indriyani, Yohanna Anisa; Rusmana, Iman; Anwar, Syaiful; Djajakirana, Gunawan; Santosa, Dwi Andreas (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Electrogenic microbes have been exploited in the microbial fuel cell (MFC) system for harvesting bioelectricity. Electrogens are widely distributed in various environments, but the exploration of this microbial group from ecosystems in Indonesia is still limited. This present study aimed to isolate the electrogenic bacteria from sediments of two waterlogged ecosystems (dam and paddy field) using serial dilution into extinction method prior to streak plate method on the solid thioglycollate media supplemented with Fe3+. Electrochemical evaluation was conducted in glucose-fed dual-chamber MFC by using Arduino UNO-based data logger for the accurate monitoring of electricity production in the term of open circuit voltage (OCV). A total of 54 electrogens were successfully isolated from these two ecosystems, ranging from weakness to strongest electrogens (OCV >800 mV) and ranging from microaerophilic, aerotolerant and facultative anaerobes, to obligate anaerobes. This result also suggested that sediment of waterlogged ecosystems rich in electron donor and solid acceptor electron compounds could potentially host electrogenic microbes. The exploration of electrogens from many other waterlogged ecosystems in Indonesia, both natural and anthropic ecosystems, could be conducted to collect genetic resources of novel electrogenic bacteria for the development of MFC technology in Indonesia.